Effects of yeast DNA topoisomerase III on telomere structure. - Kim, R A (1995)
The yeast TOP3 gene, encoding DNA topoisomerase III, and EST1 gene, encoding a putative telomerase, are shown to be abutted head-to-head on chromosome XII, with the two initiation codons separated by 258 bp. This arrangement suggests that the two genes might share common upstream regulatory sequences and that their products might be functionally related. A comparison of isogenic pairs of yeast TOP3+ and delta top3 strains indicates that the G1-3T repetitive sequence tracks in delta top3 cells are significantly shortened, by about 150 bp. Cells lacking topoisomerase III also show a much higher sequence fluidity in the subtelomeric regions. In delta top3 cells, clusters of two or more copies of tandemly arranged Y' elements have a high tendency of disappearing due to the loss or dispersion of the elements; similarly, a URA3 marker embedded in a Y' element close to the chromosomal tip shows a much higher rate of being lost relative to that in TOP3+ cells. These results suggest that yeast DNA topoisomerase III might affect telomere stability, and plausible mechanisms are discussed.